PATTERN OF PRESENTATION OF NASAL FOREIGN BODIES, AN EXPERIENCE WITH 155 PATIENTS - Sajid, Tahira; Shah, Mohammad Imran; Naqvi, Syeda Rifaat Qamar (Journal of Ayub Medical College Abbottabad, 2018)
Background: Children commonly present to outpatient department with foreign bodies in the nose. Sometimes the history is straightforward but not infrequently presentation is with a foul-smelling unilateral discharge and obstruction. Most of the foreign bodies are inert and do not cause any local tissue reaction but some of these can cause serious complications. The frequency of the different types of foreign bodies is not known in our setup. Our study aims to determine the types and frequencies of different foreign bodies in our catchment area so as to make the attending surgeon aware of the different possibilities he may have to encounter. Also, we aimed to make the general public aware of the hazards which the foreign bodies can create. Methods: This descriptive cross-sectional study was carried out at Department of ENT of Ayub Teaching Hospital Abbottabad, from 1st June to 30th November 2017. During the period of study, patients presenting in outpatient department with nasal foreign bodies were included in the study. We recorded patients’ age and gender. Types of foreign bodies recovered from the nose were documented and their frequency was calculated. Results: A total of 155 patients were included in the study. 60% of the foreign objects were inserted in the nasal passage by male children. Children below the age of 4 years comprised more than 55% of the cases. Mean age 4.5±2.36 years. Right nostril was predominantly involved (58%). Various seeds were commonly retrieved (40%). Plastic beads were the second most common foreign bodies (21.2%). Other foreign bodies found were buttons (9%), dry batteries (1.2%), stones (9%), toy pieces (4.5%), and food particles (10%). Conclusion: The commonest nasal foreign objects in children were organic seeds followed by plastic beads. Keywords: Nasal cavity; Foreign body; Airway, Airway Obstruction